Climatic Changes and Orogeneses in the Late Miocene of Eurasia: The Main Triggers of an Expansion at a Continental Scale? - Jia, Dong-Rui; Bartish, Igor V. (Frontiers in Plant Science, 2018)
Migrations from the Qinghai-Tibetan Plateau (QTP) to other temperate regions represent one of the main biogeographical patterns for the Northern Hemisphere. However, the ages and routs of these migrations are largely not known. We aimed to reconstruct a well-resolved and dated phylogeny of Hippophae L. (Elaeagnaceae) and test hypothesis of a westward migration of this plant out of the QTP across Eurasian mountains in the Miocene. We produced two data matrices of five chloroplast DNA (cpDNA) and five nuclear DNA markers for all distinct taxa of Hippophae. These matrices were used to reconstruct phylogenetic relationships in the genus. In dating analyses, we first estimated the stem node age of Elaeagnaceae using five fossil records evenly distributed across a tree of Rosales. We used this estimate and two additional fossil records to calibrate the cpDNA phylogeny of Hippophae. The same phylogeny was used to reconstruct ancestral areas within the genus. The monophyly of Hippophae, all five species, and most of subspecies was strongly supported by both plastid and nuclear data sets. Diversification of Hippophae likely started in central Himalayas/southern Tibet in the early Miocene and all extant distinct species had probably originated by the middle Miocene. Diversification of H. rhamnoides likely started in the late Miocene east of the QTP from where this species rapidly expanded to central and western Eurasia. Our findings highlight the impact of different stages in uplift of the QTP and Eurasian mountains and climatic changes in the Neogene on diversification and range shifts in the highland flora on the continent. The results provide support to the idea of an immigration route for some European highland plants from their ancestral areas on the QTP across central and western mountain ranges of Eurasia in the late Miocene.